Performance Analysis of Naàma’s 20 MW Grid-Connected Plant in Semi-Arid Climate in Algeria - Habbati Bellia Assia; Moulay Fatima (Energies)
This article is devoted to the study of a 20 MW large-scale photovoltaic power plant (LS-PVPP), connected to the grid and located in Naàma, Algeria. The power plant is included in the National Program for the Development of Renewable Energies 2015–2030. Among the parameters analyzed in detail in this work, the performance ratio recorded an average value of 67.55%, the capacity factor had an average of 17.10%, the total losses had an average of 2.10 kWh/kWp/day, the system efficiency had an average of 4.10 kWh/kWp/day and an annual average of 9.84% of the efficiency. A linear regression equation with a coefficient of determination R2 of 0.91 confirms the importance of irradiation impact in the region; less significant linearity for the effect of temperature with a coefficient of determination R2 = 0.28 is recorded for production. A comparative study conducted with the Adrar plant (Algeria) with an extremely hot desert climate and the Saida plant (Algeria) with a semi-arid climate demonstrated that the efficiency of the Naàma station is equal to 91.22% of the efficiency of Adrar and 73.47% of the efficiency of Saida. Naàma is known for its semi-arid climate; it is very cold in winter and hot in summer, with sandstorms becoming more frequent due to climate change. PVsyst software (Version 7.4.8) is used to validate the results.